Stereotypes of volunteers and nonprofit organizations' professionalization: A two‐study article. Issue 2 (29th June 2020) - Peiffer, Mathieu; Villotti, Patrizia; Vantilborgh, Tim; Desmette, Donatienne
Abstract: Competence and warmth are two fundamental stereotypical dimensions that frame people's social judgments. Since we currently lack evidence about how the volunteering workforce is socially perceived, this study aims to (a) understand which stereotypes are associated with volunteers, and (b) determine whether these perceptions vary as a result of contextual changes (i.e., professionalization) that have recently characterized nonprofit organizations (NPOs). Two empirical survey‐based studies were conducted in Belgium, one comprising data collected from a general population sample ( N = 233), and the other from volunteers ( N = 128). Study 1 displayed volunteers being perceived by the general population as warmer rather than competent. Study 2 found that ingroup warmth perceptions in a volunteers' sample decreased as NPOs became progressively more business‐like. Overall, these two studies illustrate that warmth is at the heart of the volunteers' role and show that the increasing professionalization of NPOs affects this perception.